PENGARUH GOOD CORPORATE GOVERNANCE DAN UKURAN PERUSAHAAN TERHADAP KINERJA PERUSAHAAN - Devi Nabilla Heriyani (2021)
This study aims to know the influence of good corporate governance and firm size of company performance on bank that listed on the Indonesia Stock Exchange (IDX) for the period 2016-2019. The data used in this study was from annual report. The population in this study is 40 bank that registered on idx. The sample of this study 26 bank selected with purposive sampling. The data analysis method in this study is multiple linear regression analysis using SPSS software version 25. The results of this study is board of commissioners, audit committee, independent commissioners, institutional ownership and firm size has no effect to company performance. But the simultaneous test of the board of commissioners, audit committee, independent commissioner, institutional ownership and firm size have an effect on company performance.